2017
DOI: 10.12973/ejmste/79325
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Prospective Teachers’ Perceptions Concerning the Concept of “Social Media” through Metaphors

Abstract: This study was conducted so as to determine prospective teachers' perceptions of the concept of "social media" through metaphors. The study group was composed of 138 prospective biology teachers attending Hacettepe and Gazi universities in 2015-2016 academic year. The participants were given the semi-structured interview form containing the statement "Social media is like ….. because…." And they were asked to complete the statement. The technique of content analysis was used in assessing the data collected. MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In addition, some preservice teachers viewed social media as a useless tool. When studies in literature are reviewed, similar findings were obtained in previous studies conducted with pre-service teachers from Turkey (Erdem, Alkan, & Erdem, 2017;Köseoğlu, 2018;Sendurur et al, 2015). In some studies, university students in Turkey were social media addicts at moderate and low levels (Keçe, 2016;Kırcaburun, 2016;Şahin, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…In addition, some preservice teachers viewed social media as a useless tool. When studies in literature are reviewed, similar findings were obtained in previous studies conducted with pre-service teachers from Turkey (Erdem, Alkan, & Erdem, 2017;Köseoğlu, 2018;Sendurur et al, 2015). In some studies, university students in Turkey were social media addicts at moderate and low levels (Keçe, 2016;Kırcaburun, 2016;Şahin, 2017).…”
Section: Discussionsupporting
confidence: 67%
“…Isman and Albayrak created a Facebook group for the non-elective Management of Information Technology course attended by all students in the faculty in which documents related with the lesson were shared with students through the file sharing properties of this social media application. They found that the Facebook group was beneficial in terms of its usability, contributions to group work, follow-up on announcements, and accessing more and more people (Koseoglu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These components are highly relevant to the current era, where teacher-student communication is extended to social networking sites (SNS). The use of these platforms is accompanied by potentially impactful perceptions and beliefs (e.g., Köseoğlu, 2017), is changing the way of communication de facto (e.g., Stieglitz & Dang-Xuan, 2013), and, following that, is serving as an important external factor (e.g., Mazer, Murphy, & Simonds, 2007).…”
Section: Teacher-student Relationship and Communicationmentioning
confidence: 99%